Wing-Beat Frequency and Its Acoustics in Birds and Bats. (26th June 2020) - Boonman, Arjan; Yovel, Yossi; Eitan, Ofri
Synopsis: Animal flight noise can serve as an inspiration to engineering solutions to wind-noise problems in planes or wind turbines. Here we investigate the acoustics of wingbeats in birds and bats by co-registering wing-movement in natural flight with acoustic noise. To understand the relationships between wing movement and acoustics, we conducted additional acoustic measurements of single moving wings and other moving surfaces with accurately tracked motion paths. We found a correlation between wing-surface area and the sound pressure level of wingbeats; with bats tending to produce lower levels than birds. Measuring moving wings in isolation showed that a downstroke toward a microphone causes negative sound pressure that flips back into positive pressure at the reversal to the upstroke. The flip back to positive pressure is unrelated to the action of the upstroke, but occurs when the downward motion is halted. If the microphone is positioned above the downward wingbeat, then sound pressure instead quickly rises during the downward motion of the wing. The phase pattern of the impulse created by the wingbeat varies systematically with recording-angle. The curvature of the wing appears to be a determinant of the average frequency of the acoustic impulse. Our findings can be used to predict the acoustics of smaller flying animals where repetition pitch of similar underlying impulses, repeated at much higher wingbeat-rates become dominant.